Gambaran Sanitasi Lingkungan di Pasar Oeba Kecamatan Kota Lama Kota Kupang - Irene Maria Bili; Yuliana Radja Riwu; Soleman Landi (Media Kesehatan Masyarakat, 2021)
Market sanitation is an effort to supervise, prevent, and control the quality of the market environment, especially those that can transmit diseases such as flies. The density of flies can increase if the environment of markets does not meet the sanitation requirements. Oeba traditional market is one of the markets in Kupang City that has the highest density of flies with an average of 21 blocks/30 seconds of block grill. The purpose of this research is to describe the environmental sanitation of Oeba Market, Kota Lama Sub-district, Kupang City in 2020. The research was descriptive. The population in this study were all selling sections located in the market from which the sample of fish, meat and vegetable sections were selected using purposive sampling method. The density of flies was measured using a fly grill tool. Data were analyzed descriptively. The results showed that the availability of environmental sanitation at the fish selling section was categorized as quite good with an average fly density level of 2 heads/block grill, the meat section was categorized as poor with the density level of 10 fly/block grill and the vegetable/fruit section was categorized as poor with the density of 2 flies/block grill. A collaboration among the government and the local community both traders and market managers is necessary to ensure to the environmental sanitation of the market.